Generalized eczematous dermatitis and pruritus responsive to dupilumab in a patient with immune dysregulation, polyendocrinopathy, enteropathy, X‐linked (IPEX) syndrome. Issue 5 (16th July 2021) - Maher, Maeve C.; Hall, Erin M.; Horii, Kimberly A.
Abstract: This case describes a patient with immune dysregulation, polyendocrinopathy, enteropathy, X‐linked (IPEX) syndrome with diffuse eczematous dermatitis and severe, intractable pruritus. Despite a bone marrow transplant and immunosuppressive therapy, his skin findings and pruritus persisted. Off‐label dupilumab provided significant improvement and almost complete clearance of the dermatitis and pruritus. This is the first known report of dupilumab being used in a patient with IPEX syndrome.